'Even Seneca hymselfe to speke in englysh': John Studley's Hippolytus and Agamemnon. (March 2020) - Valls-Russell, Janice
Abstract : John Studley translated four of Seneca's plays into English: Agamemnon, Medea, Hippolytus (as Phaedra was known in the Renaissance), and Hercules Oetaeus, and these were later included in Thomas Newton's collection Seneca His Tenne Tragedies, 1581. This essay focuses on Studley's Hippolytus, with intersecting discussions of his Agamemnon . It looks at the Latin texts and commentaries Studley may have been using, and shows that his translation incorporates elements of intertextuality and imitation that expand on Seneca's own engagement with Ovid. Tracing how Seneca's and Studley's characters find models and counter-models in other mythological figures, the discussion draws attention to Studley's foregrounding of generational confusion, and his handling of gender.